Michel Foucault and Philosophical Modernity - shaker, makhlouf (Journal of Social Sciences and Humanities, 2016)
The field of values within modern temporality is characterized by relativism and change, as well as by the critique of references and fixed foundations that once represented the self-evident principles of moral reason in the pre-modern era. All of this points to the nature of modernity and to what its fundamental trait imposes: the necessity of continuous critique and perpetual change. Modernity, in its ontological determination, is a rapidly evolving and transformative time, grounded in the effectiveness of rational critique as well as in cultural dimensions and the historical presence of the human being. Modernity is not limited to the successive transformation of human practical life; it also extends to an epistemological critique of human cognitive capacity, in both its rational and empirical representations, thereby transcending any imposed epistemic authority except that which arises from reason itself. This transformation led to the affirmation of man as master and possessor of nature. This form of sovereignty imposed a radical shift in practical life and intellectual horizons, and also enabled profound civilizational transformations in the contemporary world. As a result, divergent positions emerged regarding the value of modernity and what it has produced for humanity. We find that postmodern philosophy, in most of its trends, has adopted a critical stance toward it. In this article, we will focus on the position of the French philosopher Michel Foucault. What is Michel Foucault’s stance on philosophical modernity? How did he read Descartes as the father of modern philosophy? How did Foucault resume critique starting from Kant? And what place does Hegel occupy within Foucault’s philosophy?